Kurang Energi Kronis Pada Ibu Hamil di Kota Pekalongan - Zaenal Amirudin; Bagoes Widjanarko; Martha Irene Kartasurya (Jurnal Promosi Kesehatan Indonesia, 2011)
Protein Energy Malnutrition (PEM) in Pekalongan is still quite high, 11.95% and affects most of one’s life, which began in fetus in the womb, infancy and continue until the child enters school age. This research is to analyze the incidence of risk factors in pregnant woman PEM. A total of 76 samples comprising 38 cases and 38 controls were recruited in this study. Upper Arm Circumference was measured in pregnant woman and used a structured questionnaire to obtain information about predisposing factors such as knowledge, attitudes, eating habits and abstinence of certain foods. The results showed that maternal attitudes toward nutrition (p=0.02) and eating habits of pregnant woman (p = 0.03) significantly influenced the incidence of PEM. Analysis of risk factors for maternal nutrition knowledge (p=0.3) and abstinence from food to pregnant woman (p = 1.0) obviously has no effect on the incidence of PEM.